La dinámica familiar y su relación con la adquisición de destrezas con criterio de desempeño en el eje del desarrollo personal y social de los niños y niñas del primer año de educación básica de la escuela Gabriela Mistral nº 1 del cantón Catamayo, de la provincia de Loja, periodo lectivo 2012-2013 - Narea Castillo, Lourdes Gabriela (2014)
The present thesis whose title is: "THE FAMILY DYNAMICS AND THEIR RELATIONSHIP WITH THE ACQUISITION OF DEXTERITY WITH APPROACH OF ACTING IN THE AXIS OF THE PERSONAL AND SOCIAL DEVELOPMENT OF THE CHILDREN and GIRLS OF THE FIRST YEAR OF BASIC EDUCATION OF THE SCHOOL "GABRIELA MISTRAL Nº 1" OF THE CANTON CATAMAYO, OF THE COUNTY DE LOJA, PERIOD 2012 - 2013" was developed based in regulation the Academic Regimen of Régime of the National University of Loja. The general objective outlined in the thesis project was to Investigate the family existent dynamics and its relationship with the development of dexterity in the axis of the children's of the first year of Basic Education of the school personal and social development "Gabriela Mistral Nº 1" school Catamayo Cantón. This investigative work is descriptive character, the methods used were: Scientific, Inductive-deductive, Synthetic and Descriptive, and; the statistical pattern. The techniques used were: the Survey that was applied the family parents to know the type of family existent dynamics in their home and, the observation Guide applied the children and girls to know the acquisition of dexterity with acting approach in the axis of personal and social development. With the application of the survey became known that one hundred percent of parents surveyed report that in their family dynamics Family Adaptability and Family Cohesion Communications evidenced. The family type in which is born and a boy is raised it affects significantly to the beliefs, values, expectations, lists, behaviors, and interrelate that he will have throughout his life. Of the application of the observation guide it was determined that 84% of evaluated children has acquired dexterity with acting approach in the axis of the personal and social development that you/they are equal to very satisfactory; while 15% of children has acquired dexterity with acting approach in this axis that you/they are equal to satisfactory; while 5% of children has acquired dexterity with acting approach in the mentioned axis of the learning that you/they are equal to not very satisfactory That makes deduce that these children and girls possess a personal and social good development, regarding acquisition of dexterity with approaches of acting that their development has been carried out in function of the existent different family relationships in each home